Identification of Large-Scale Travelling Ionospheric Disturbances (LSTIDs) Based on Digisonde Observations - Ioanna Tsagouri; Anna Belehaki; Konstantinos Koutroumbas; Konstantinos Tziotziou; Themistocles Herekakis (Atmosphere, 2023)
In this paper we analyze Digisonde observations obtained in the European region to specify the effects of large-scale travelling ionospheric disturbances (LSTIDs) on the ionospheric characteristics that define the conditions in the bottomside ionosphere. While this type of disturbances affects all frequency ranges in the F region, the most pronounced effect is detected in the foF2 critical frequency, where the density is the highest. During LSTID activity, a significant uplifting of the F2 layer is observed to accompany an oscillation pattern in the foF2. Concurrent variations in the height of the peak electron density hmF2 and the corresponding scale height, Hm are also observed. These findings are used to propose a new methodology for the identification of LSTIDs, comprising a combination of different criteria. The efficiency of the proposed methodology is tested at middle latitudes during geomagnetically quiet and disturbed intervals as well as during time periods of lower atmosphere forcing affecting the ionosphere.